The COVID-19 Pandemic and Changes in Nursing Care Interventions in 2020 and 2021 in the Brazilian Amazon - Mônica Borchart Nicolau; Patrícia dos Santos Vigário; Alvaro Camilo Dias Faria; Thiago Thomaz Mafort; Igor Ramathur Telles de Jesus; Agnaldo José Lopes (Hindawi Limited, 2024)
Conclusion: Patients with COVID-19 experienced an increase in nursing care from 2020 to 2021 across all evaluated organ systems, indicating that nursing care improved as knowledge about the pandemic was gained.